Prophetic Leadership in Creating Superior Educational Institutions: Phenomenological Study of Private Islamic Universities - Hefniy, Hefniy; Mardiana, Dina; Enggal, Dwi; Baharun, Hasan (JURNAL AL-TANZIM, 2023)
This research focuses on the prophetic leadership style practised in two higher education institutions, namely Nurul Jadid University Probolinggo and Muhammadiyah University Malang. This prophetic leadership style is a leadership style that can develop, encourage and create superior (Islamic) educational institutional units that have other prestigious educational qualities. This research uses a qualitative approach with a case study type of research to understand the leadership phenomenon in these two sites. Data were collected through interviews, participant observation, and documentaries. Next, the data was analyzed using Miles, Hubermann and Saldana interactive analysis. This research concludes that the leaders of the FAI UNUJA and FAI UMM institutions have a prophetic leadership style, which is demonstrated through their roles as quality control, political power, and political will (goodwill). From this leadership style, prophetic nuances emerge in institutional governance, which refers to 4 (four) pillars: theological-monotheistic, empirical-demonstrative, rational-philosophical, and theoretical stakes. The four pillars of prophetic management in the two research sites ultimately gave birth to a prophetic leadership style, which is essentially based on the three epistemological frameworks of Burhani, Bayani, and Irfani.